Social recovery: a new interpretation to recovery-orientated services – a critical literature review. Issue 1 (29th October 2020) - Norton, Michael John; Swords, Calvin
Abstract : Purpose: In 2020, the significance of "lived experience" and "service user" accounts of recovery has become central to the delivery of mental health policy and practice. Reflecting on the first known account of personal recovery in the late-20th century provided new hope and encouragement that those living with mental illness could live a fulfilling life. Taking this into consideration, the purpose of this paper is to explore the relevance to this experience of those using services today. Design/methodology/approach: The authors present a critical literature review, which is underpinned by a systematic approach adopted from Higgins and Pinkerton (1998). This involved a six-step approach seeking to answer the question – What are the service users' views on the recovery concept within mental health services? Findings: The conceptualisation of recovery continues to focus on biomedical parameters. A new interpretation of recovery is beginning to materialise: social recovery. This new interpretation appears to be achievable through six key influencers: health, economics, social interaction/connection, housing, personal relationships and support. Originality/value: Building on Ramon's (2018) argument regarding the need for mental health policy to focus on the concept of social recovery, this study extends on this proposition by providing a foundational evidence base. More specifically, it not only supports the need for this shift in policy but also identifies a new interpretation building in practice. Furthermore, the authors highlight six key pillars that could potentially shape such provisions for policy.